2015
DOI: 10.1007/s00167-015-3724-3
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy between morphological findings in juvenile osteochondritis dissecans (OCD): a comparison of magnetic resonance imaging (MRI) and arthroscopy

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 22 publications
0
15
0
2
Order By: Relevance
“…In a study that compared MRI with arthroscopic findings in 17 juvenile patients with ankle cartilage lesions, MRI and arthroscopy correlated in 65% of cases. 10 Although a diagnostic CT or MRI scan is typically obtained with the ankle in a plantigrade position, a CT scan with the ankle in full plantar flexion has also been described for preoperative planning 13,14 and may be considered useful in the operative planning of lesions localized to the posterior half of the talus and in ankles with limited range of motion.…”
Section: Discussionmentioning
confidence: 99%
“…In a study that compared MRI with arthroscopic findings in 17 juvenile patients with ankle cartilage lesions, MRI and arthroscopy correlated in 65% of cases. 10 Although a diagnostic CT or MRI scan is typically obtained with the ankle in a plantigrade position, a CT scan with the ankle in full plantar flexion has also been described for preoperative planning 13,14 and may be considered useful in the operative planning of lesions localized to the posterior half of the talus and in ankles with limited range of motion.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly found in the knee, plain radiographs are used reliably for diagnosis, staging [ 2 ], and management. Advanced imaging, such as MRI, is often used in conjunction with radiographs and physical exam for staging and surgical planning though inconsistencies in protocols and findings limit its clinical utility [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…42 Heywood et al 43 reported a specificity of 15% for diagnosing fragment instability. In a recent study from Germany, 44 the authors found a poor correlation between pre-operative MRI and arthroscopy morphological findings (59.6% of all patients with an OCD of the femoral condyle). Both studies agree that MRI should not be used in isolation to determine lesion stability in young patients with juvenile OCD.…”
Section: Imagingmentioning
confidence: 91%